Genomic selection for lucerne biomass yield in di erent stressprone environments - Annicchiarico, Paolo; Nazzicari, Nelson; Pecetti, Luciano; Hayek, Taoufik; Bouizgaren, Abdelaziz; Laouar, Meriem; Brummer, Edward Charles; Cornacchione, Monica; Basigalup, Daniel Horacio (Wageningen Academic Publishers, 2024)
Trabajo presentado en: Improving sown grasslands through breeding and management. Proceedings of the Joint 20th Symposium of the European Grassland Federation and the 33rd Meeting of the EUCARPIA Section ‘Fodder Crops and Amenity Grasses’ Zürich, Switzerland 24-27 June 2019